Imagining an 'ideal school': an approach for reflecting on principals' educational creed. Issue 1 (2nd January 2016) - Zur, Ayala; Eisikovits, Rivka A.
Abstract: In this paper, we describe an approach to the study and development of school principals' school creed. The approach and its underlying method are grounded in the phenomenological tradition, predominantly in the philosophy of Merleau-Ponty. School principals are asked to imagine an ideal school and present it both visually and verbally. We illustrate the potential of this process using one ideal school proposal developed by a high school principal in Israel. The paper concludes with a discussion of the implications of the approach for research, theory and practice.